Hubungan Pengetahuan Ibu tentang Diare dan Pola Asuh Ibu dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Tanjung Rejo (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Diarrhea is a health problem in Indonesia that can cause death in toddlers. Weak immune system causes toddlers attacked by diarrhea easily. Factors affecting diarrhea in toddlers are mother’s knowledge, parenting and environmental sanitation. This study aimed to determine the correlation between mother's knowledge of diarrhea and parenting with the incidence of diarrhea in toddlers. The design of this study used Cross sectional with 36 subjects of toddlers affected by diarrhea. The results were analyzed using Rank spearman correlation test and multiple linear regression test. There is a negative and significant correlation between mother’s knowledge of diarrhea and the incidence of diarrhea in toddlers, means that the lower mother's knowledge of diarrhea, the higher the incidence rate of diarrhea (Rs = -0.47). There is a negative and significant correlation between mother’s parenting and the incidence of diarrhea in toddlers, means that the lower mother’s parenting, the higher the incidence of diarrhea (Rs = -0.647). There is a negative and significant correlation between mother’s knowledge about diarrhea and parenting with the incidence of diarrhea in toddlers (Y = 4.009 – 0.114x1-0.056x2), means that the lower mother's knowledge of diarrhea and parenting, the higher the incidence of diarrhea in toddlers.